Functional properties of pumpkin seed flour for use in bakery products - Shevchenko, Anastasiia (My University, 2022)
Pumpkin processing products contribute to reducing the risk of inflammatory processes of the gastrointestinal tract, and are also recommended for diet therapy in the case of these diseases. The water-absorbing and moisture-retaining capacity of pumpkin seed flour is higher tham wheat flour, so it is needed more water to form elastic dough. It is predicted that the moisture will be well retained, and therefore the gluten subunits will be properly connected to each other and form a strong framework.
Keywords: pumpkin seed flour; dough; bakery product; water absorbing capacity; water holding capacity; fat absorbing capacity; fat holding capacity; emulsifying ability; emulsion stability; кафедра технології хлібопекарських і кондитерських виробів